THE STRUCTURE AND THE PURPOSE OF CREATING EUROPEAN POLICE OFFICE (EUROPOL) - TĂRCHILĂ, Petru (International Journal of Legal and Social Order, 2022)
The purpose of creating Europol was to improve police cooperation in the field of organised crime at international level. Europol's objectives are to improve the effectiveness of the competent services of the Member States and cooperation in preventing and combating terrorism, drug trafficking and other serious forms of international crime where there are indications that a criminal structure or organisation exists and where two or more Member States are affected by these forms of crime in a way which, by reason of the scale, seriousness and consequences of the offences, requires joint action by the Member States